Agreement and bias in the estimation of fat free mass using bioelectrical impedance analysis and a resistance and reactance- based formula for the Mexican adults: A study from Merida, Yucatan - Banik, Sudip Datta (Acta Biologica Szegediensis, 2021)
Bioelectrical impedance analysis (BIA) is used to estimate body composition characteristics. The values of body fat and fat free mass (FFM) are obtained as per algorithms of the device that are often unknown to the researchers. Some models of the analyzer provide resistance and reactance values that may be useful to estimate FFM. Objective of the present study was to test the agreement and proportional bias in the estimation of FFM obtained through BIA and that derived from the resistance and reactance values using a formula for Mexican adults. A cross-sectional study was carried out in 2019 selected 60 university male students aged 21 to 23 years from Merida, Yucatan. A multifrequency whole body bioelectrical impedance analyzer Tanita MC 180 MA (Tanita Corporation, Tokyo-Japan) was used to evaluate body composition characteristics. The device gives estimates of FFM in kg (based on algorithm) and the resistance and reactance values (ohms). There is an existing formula for Mexican adults to estimate FFM (FFM_FOR) from the resistance and reactance values obtained through BIA. An agreement between the two estimates of FFM has been tested using Bland-Altman plot and linear regression analysis. Mean value of age of the participants was 21.88 years. FFM estimated by BIA (FFM_BIA = 41.44 kg) and that derived from FFM_FOR (41.36 kg) had signifi cant intraclass correlation coeffi cient (ICC) (Cronbach’s alpha = 0.99, p<0.0001). One sample t-test estimating the diff erence of mean values between FFM_BIA and FFM_FOR was not signifi cant (t = 1.37, mean diff erence -0.02, p = 0.18). The Bland-Altman plot shows almost all data points lie within 95% confi dence interval limits. A linear regression analysis using the diff erence of FFM values as dependent variable and the average of the measurements as the independent variable showed no signifi cant interrelationships. In conclusion, the formula to estimate FFM using the resistance and reactance values of BIA has been found to be useful in the present study.